2007
DOI: 10.1158/0008-5472.can-06-3608
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Angiogenic Phenotype Alters Tumorigenicity in Rat Ovarian Epithelial Cells

Abstract: Vascular endothelial growth factor (VEGF) expression correlates with microvessel density, stage, malignant ascites, metastasis, and survival in ovarian cancer. By transducing VEGF165 into a nontumorigenic rat ovarian surface epithelial cell line (ROSE199), we investigated the direct effect of an angiogenic phenotype on tumor development. The neu oncogene, which is overexpressed in >30% of ovarian cancers, was used in comparison. Neu-transfected ROSE199 cells showed phenotypic characteristics of transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Furthermore CD31 staining of the tumor tissues of AuNP-treated mice also demonstrated a reduction in the number of tumor blood vessels compared with NT mice, consistent with the inhibitory effect of AuNPs toward HB-GF (Fig. 3 F and G) (45)(46)(47). Moreover, AuNP-mediated reversal of EMT and abrogation of MAPK activation leading to inhibition of tumor growth and metastasis was further confirmed by analysis of tumor tissues by Western blot analysis (Fig.…”
Section: Aunp Treatment Inhibits Tumor Growth and Metastasis In Vivo Bysupporting
confidence: 73%
“…Furthermore CD31 staining of the tumor tissues of AuNP-treated mice also demonstrated a reduction in the number of tumor blood vessels compared with NT mice, consistent with the inhibitory effect of AuNPs toward HB-GF (Fig. 3 F and G) (45)(46)(47). Moreover, AuNP-mediated reversal of EMT and abrogation of MAPK activation leading to inhibition of tumor growth and metastasis was further confirmed by analysis of tumor tissues by Western blot analysis (Fig.…”
Section: Aunp Treatment Inhibits Tumor Growth and Metastasis In Vivo Bysupporting
confidence: 73%
“…These findings point to an additional important role for VEGF in ovarian cancer invasion. VEGF plays a critical role in ovarian cancer progression by enhancing vascular permeability, promoting new vessel growth and inducing ascites formation, and hence, tumor cell dissemination (22). In addition, this study shows that by promoting host MMP9 expression, tumor VEGF enhances the tumor cell's invasive potential.…”
Section: Discussionmentioning
confidence: 63%
“…Opipari and colleagues (2004) has shown that resveratrol induces death in ovarian cancer cells by autophagocytosis, a mechanism distinct from apoptosis, suggesting that it may provide leverage to treat ovarian cancer that is chemoresistant on the basis of ineffective apoptosis. Further, alterations in the angiogenic characteristics of ovarian surface epithelium may play an important role in the etiology of ovarian cancer (Schumacher et al, 2007). Human ovarian cancer progression and angiogenesis were reduced by resveratrol through suppression of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) as observed (Cao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%